Cultural Americanism at the end of the 19th century: Spain, America and the circulation routes of the Spanish and American book - Pasquaré, Andrea (Meridional. Revista Chilena de Estudios Latinoamericanos, 2024)
To commemorate the four hundred years of the Discovery of America, the Hispanic-American Literary Congress was held in Madrid, organized by the Association of Spanish Writers and Artists, with the purpose of building bridges of union and exchange of Hispanic and American cultural products, allocating the marketing of Spanish books in Spanish America plays a central role. The increasing presence of publications in Spanish from other European publishers, coming mainly from France, and secondly, from England and Germany, made them aware of the necessary and urgent presence of Spain in controlling the American market. To the demand of individuals (businessmen and merchants, writers, political class) gathered in Americanist associations that demanded cultural policies that encompass the circulation and exchange of Spanish books in America, was added that of the historian and jurist Rafael Altamira who sought to integrate through its Americanist propaganda work, those editorial exchanges with a cultural policy of joint action that would facilitate dialogue and the definition of common programs between Spain and Spanish America.